Regulatory framework for the formation of information culture of modern Kazakhstan youth - Myrzakhmetova, А.Zh.; Khlebnikov, I.D.; Rezvushkina, Т.А.; Karaseva, N.V. (KSU Publ., 2020)
The article analyzes the regulatory framework for the formation of the information culture of modern Kazakhstan youth. The authors present the main components that form the general information culture of society, including information, media and digital literacy, digital infrastructure. Researchers have identified the main areas of state activity, which reflects this problem, namely state policy in the field of creation and development of the state information infrastructure, e-government, educational and media policy, cyber security and child safety. The article also provides an overview of international legislation and international regulatory experience, from the 1982 Grunewald Declaration of UNESCO to the Council of Europe Strategy for the Rights of the Child (2016–2021). The current situation in Kazakhstan is confirmed by official statistics of the Committee of Statistics of the Republic of Kazakhstan. The authors conclude that not all spheres of the formation, development and regulation of the information culture of Kazakhstan society, including youth, are in the focus of attention of state structures. Some measures are taken late, or do not have specific mechanisms for functioning and implementation. According to the authors, in the context of the COVID-19 pandemic and, consequently, the transition to distance learning, more than 90 % of Kazakhstan children turned out to be active users of information and communication technologies, daily encountering all the opportunities and potential threats posed by the global Internet.
Қазіргі қазақстандық жастардың ақпараттық мəдениетін қалыптастырудың нормативтік-құқықтық негіздері
Нормативно-правовые основы формирования информационной культуры современной казахстанской молодежи
Keywords: information culture; information and digital literacy; media literacy; digital infrastructure; security; state regulation; «Digital Kazakhstan»; state regulation; legal acts